Assessment of groundwater potential zones using GIS and AHP techniques – A case study of the zone of influence of Kolubara Mining Basin - Živanović Milica; Milanović Miško M.; Momirović Natalija; Tomić Milisav; Kričković Emina (Open Geosciences)
Groundwater forms through infiltration beneath the Earth’s surface as it moves through various rock layers. Reliable and sustainable water supplies are predominantly sourced from underground sources, making them some of the most important natural resources. The aim of this study is to assess and identify potential groundwater zones using Geographic Information Systems, remote sensing, and multi-criteria analysis, specifically the Analytical Hierarchy Process (AHP), within the Kolubara Mining Basin influence zone in Serbia. This study considers factors such as rainfall, geology, slope, river network density, and land use/land cover. These factors were evaluated using the Saaty scale to determine their respective weights. Due to their higher weights, the AHP process revealed that precipitation and geology are the most influential factors in groundwater formation. Groundwater potential zones are categorized into five classes: very low, low, moderate, high, and very high. These results will enhance groundwater management at both regional and local levels and contribute to the future protection of this resource.